Conservation situation and social network analysis of industrial heritage in Tangshan City / China Li Aimin and Wahiza Abdul Wahid - Li Aimin, China; Abdul Wahid, Wahiza (Faculty of Art and Design, 2023)
Due to rapid urbanization development, industrial heritage is gradually being replaced by luxury residential buildings. Heritage is an asset of collective interests and made up of inherited tangible and intangible attributes. Since the late twentieth century, much attention has been paid to the analysis of industrial heritage, as it stands witness to the significant influence of industrial civilization on the economy, social development, and human production. The objectives of this research are to evaluate the economic, cultural, and historical values of industrial heritage in Tangshan, China and renew this heritage from the perspective of the cultural industry. Combination analysis of qualitative and quantitative methods is used to reflect the conservation situation of industrial heritage in this city and also evaluate the accessibility of these heritage to show their potential for renewal based on the data from surveys and statistical yearbooks. The results show that the present situation of the conservation of industrial heritage in Tangshan is developing rapidly, and the cultural industry becomes not only an attractive means for promoting the development of iron and steel, coal mining, and cement industry, but also inheriting industrial culture of these industries. Meanwhile, based on the quantitative analysis results, indicating that Kailuan Coal Mine and Tangshan Railway Site receive the highest concern from the government from the perspective of transportation for their conservation and renewal. This research can provide scientific basis for the value assessment and future renewal of industrial heritage for other heavy industry-based regions.